Implosion-explosion in supernovae. (4th March 2020) - Chavanis, Pierre-Henri; Denet, Bruno; Le Berre, Martine; Pomeau, Yves
Abstract: We sketch a scenario for the explosion of massive stars (supernovae) that differs from published scenarios of explosions as a two-step process, an initial gravitational core collapse followed by an expansion of matter after a bouncing on the core, which meet difficulties. Our simple model, based on fluid mechanics and stability properties of the equilibrium state, shows that one can have a simultaneous inward/outward motion in the early stage of the instability of the star. This shows up by slowly sweeping a saddle-center bifurcation found when considering equilibrium states associated with the constraint of energy conservation (microcanonical ensemble) instead of the constraint of a fixed temperature (canonical ensemble). After the weakly nonlinear Painlevé regime, we show that the strongly nonlinear regime displays a self-similar behavior of the core collapse. Finally, the expansion of the remnants is revisited as an isentropic process leading to shocks formation.